Communities of Niche-Optimized Strains: Small-Genome Organism Consortia in Bioproduction. Issue 2 (February 2019) - Noack, Stephan; Baumgart, Meike
Abstract : Bacterial genome reduction is a common phenomenon in nature that has also inspired several projects with biotechnologically relevant organisms. In many cases, however, no performance improvements with the streamlined chassis were obtained. A comparative analysis of natural and synthetic reduced genomes and their corresponding ecological niches reveals that: (i) deleting expressed genes can lead to noticeable energy conservation usable for improved biomass or product synthesis; and (ii) the simplified strains depend on the environment (e.g., another community member) to complement deleted functions. Based on this analysis, we introduce the concept of Community of Niche-optimized Strains (CoNoS) as an alternative strategy to generate superior biotechnological production processes. Highlights: Genome reduction is a common phenomenon in nature, not only in symbionts or pathogens but also in free-living organisms. Natural communities of genome-reduced strains share common goods that allow optimal use of the available resources. Synthetic genome reduction aims for minimal cells to solve fundamental questions or for streamlined chassis to improve biotechnological production. Chassis streamlining cannot lead to significant performance improvements if genome reduction focuses only on irrelevant genes with low expression levels.